Cost sharing in the social sectors of Sub-Saharan Africa : impact of the poor - Adams, Arvil V.; Hartnett, Teresa (Washington, D.C. : World Bank, 1996)
This study reviews the African Region of the World Bank's current thinking on cost sharing and the poor as applied in Sub-Saharan Africa.
Includes bibliographical references (p. 41-44).
osc 05/08/16
Loans
Keywords: Human services -- Costs; Poor--Services for--Costs; Poverty; Poor; Africa, Sub-Saharan.